Obserwator wobec barier poznawczych = The observer towards to cognitive barriers - Saja, Krystian (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The purpose of this article is to prove the thesis of the possibility of rejection of anthropocentrism as the basic point of reference in the process of perception. It can be observed that barrier of anthropic reference point may cause a great damage in the preferred that is why, it can be said that focusing on the historical facts about the difficulties with accepting the idea of a heliocentric scientific objectivity. However, the quantum mechanics gives us the evidence of the possibility to reject that, due to the fact that defining the unique role of the observer in the process of studying about physical reality. What is more, in this piece of writing the thesis about science and human life, might be treated as a mathematical process, based on achieving the specific purpose. All in all, in this way the figure called an external observer is created and it exists as the outside observer.
Keywords: kognitywizm